Acute and chronic infection: Is there a gold standard for management of the wound and bone defect?. Issue 1 (March 2020) - Giannoudis, Peter V.; Tosounidis, Theodoros H.
Abstract : Abstract: Acute and chronic infections with bone involvement remain a challenge to manage. They pose a significant burden to the patient, the treating surgeon, and society. Multidisciplinary team involvement is mandatory for a successful outcome. Application of a gold standard approach is not possible due to the high heterogeneous patient population and the variable degree of severity of soft tissue and bone involvement. The mainstay of treatment remains the conversion of a septic environment to an aseptic one with aggressive debridement of the affected soft tissues and bone. Reconstruction of the soft tissue defect can be achieved using modern microsurgical techniques, whereas the induced membrane and distraction osteogenesis (bone transport) are currently the 2 most commonly used treatment modalities for bone loss. The safest approach to deal successfully with this multifaceted clinical pathology is to always follow well-established principles of management and adapt treatment to the personalized needs of the patient.